The antimicrobial and antibiofilm effects of gentamicin, imipenem, and fucoidan combinations against dual-species biofilms of Staphylococcus aureus and Acinetobacter baumannii isolated from diabetic foot ulcers - Mohsen Nazari; Mohammad Taheri; Fatemeh Nouri; Maryam Bahmanzadeh; Mohammad Yousef Alikhani (BMC, 2024)
Abstract Introduction Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia due to impaired insulin production or utilization, leading to severe health complications. Diabetic foot ulcers (DFUs) represent a major complication, often exacerbated by polymicrobial infections involving Staphylococcus aureus and Acinetobacter baumannii. These pathogens, notorious for their resistance to antibiotics, complicate treatment efforts, especially due to biofilm formation, which enhances bacterial survival and resistance. This study explores the synergistic effects of combining gentamicin, imipenem, and fucoidan, a sulfated polysaccharide with antimicrobial properties, against both planktonic and biofilm forms of S. aureus and A. baumannii. Methods Isolates of S. aureus and A. baumannii were collected from DFUs and genetically confirmed. Methicillin resistance in S. aureus was identified through disk diffusion and PCR. Biofilm formation, including dual-species biofilms, was analyzed using the microtiter plate method. The antimicrobial efficacy of gentamicin, imipenem, and fucoidan was assessed by determining the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), minimum biofilm inhibitory concentration (MBIC), and minimum biofilm eradication concentration (MBEC). Synergistic interactions were evaluated using the fractional inhibitory concentration index (FICi) and fractional bactericidal concentration index (FBCi). The expression of biofilm-associated genes (icaA in S. aureus and bap in A. baumannii) was analyzed, and the cytotoxicity of fucoidan was assessed. Results The study revealed that 77.4% of S. aureus and all A. baumannii isolates showed multidrug resistance. Among 837 tested conditions for dual-species biofilm formation, 72 resulted in strong biofilm formation and 67 in moderate biofilm formation. The geometric mean MIC values for gentamicin were 12.2 µg/mL for S. aureus, 22.62 µg/mL for A. baumannii, and 5.87 µg/mL for their co-culture; for imipenem, they were 19.84, 9.18, and 3.70 µg/mL, respectively, and for fucoidan, 48.50, 31.20, and 19.65 µg/mL, respectively. The MBC values for gentamicin were 119.42, 128, and 11.75 µg/mL; for imipenem, they were 48.50, 14.92, and 8 µg/mL; and for fucoidan, they were 88.37, 62.62, and 42.48 µg/mL. The MBIC values were 55.71, 119.42, and 18.66 µg/mL for gentamicin; 68.59, 48.50, and 25.39 µg/mL for imipenem; and 153.89, 101.49, and 53.53 µg/mL for fucoidan. The MBEC values were 315.17, 362.03, and 59.25 µg/mL for gentamicin; 207.93, 157.58, and 74.65 µg/mL for imipenem; and 353.55, 189.46, and 99.19 µg/mL for fucoidan. When cultured in planktonic form, the geometric mean FICi and FBCi values indicated additive effects, while co-culture showed FICi values of ≤ 0.5, suggesting a synergistic interaction. Treatment with gentamicin and fucoidan led to significant downregulation of the icaA and bap genes in both single-species and dual-species biofilms of S. aureus and A. baumannii. The reductions in gene expression were more pronounced in dual-species biofilms compared to single-species biofilms. Additionally, treatment with imipenem and fucoidan also resulted in significant downregulation of these genes in both biofilm types. Cytotoxicity assessments indicated that higher concentrations of fucoidan were toxic, yet no harmful effects were noted at the optimal synergistic concentrations used with antibiotics. Conclusion In our investigation, we found that combining gentamicin, imipenem, and fucoidan had a synergistic effect on dual-species biofilms of S. aureus and A. baumannii, suggesting potential benefits for treating such infections effectively. This underscores the importance of understanding microbial interactions, antibiotic susceptibility, and biofilm formation in DFUs.